2014
DOI: 10.4172/2324-8785.1000211
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fine Needle Aspiration Cytology (FNAC) as a Diagnostic Tool in Paediatric Head and Neck Lymphodenopathy

Abstract: A neck mass that is present for longer than a week might be pathological requiring rapid and thorough evaluation. This study aims to evaluate the positive role Fine needle aspiration cytology plays in the diagnosis of pediatric patients with lymphadenopathy in the head and neck region. Fine needle aspiration of lymph nodes was carried out, fixed and stained by cytopathologists for 56 patients at the Jos University Teaching Hospital, 43 (76.8%) were inflammatory and 13 (23.2%) malignant. Reactive hyperplasia (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
(7 reference statements)
2
3
0
Order By: Relevance
“…15 Hematologic malignancies are far more frequent in pediatric patients than in adults. 18 In our study mean patient age for metastatic SLN was 64.5 years, and hematologic malignancies were also seen in aged patients. Breast cancer occurred in younger patients (mean: 52.2).…”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…15 Hematologic malignancies are far more frequent in pediatric patients than in adults. 18 In our study mean patient age for metastatic SLN was 64.5 years, and hematologic malignancies were also seen in aged patients. Breast cancer occurred in younger patients (mean: 52.2).…”
Section: Resultssupporting
confidence: 46%
“…Patient age should also always be considered. [18][19][20] Metastatic cases are most often seen over the age of 45-50 years 12,21 and lymph nodes from pediatric patients usually show reactive lymphadenitis. 15 Hematologic malignancies are far more frequent in pediatric patients than in adults.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Similar to the study by Paliwal etal, Cyto diagnosis of granulomatous lymphadenitis was more (56.8%) in our study whereas reactive hyperplasia was the common findings in some studies. 8,9,10 Similar to the study by sunali gupta, our study also showed sex predilection of female predominance for granulomatous adenitis (63.1%) and reactive adenitis (62.5%) for male children. 11 No malignancies were observed in our study whereas some studies showed malignant diagnosis in childhood lymphadenopathy.…”
Section: Discussionsupporting
confidence: 89%
“…One fourth of reactive hyperplasia in FNAC was actually lymphomas on lymph node biopsy. There were no false positive cases of malignancy on FNAC [21] but there was discordance in one case where lymphoproliferative picture on FNAC turned out to be metastatic neuroendocrine cancer on histopathology. Our study reported a low sensitivity for FNAC with discordance rate of 20.3% between FNAC and biopsy.…”
Section: Discussionmentioning
confidence: 90%